Intelligent evaluation method for design education and comparison research between visualizing heat-maps of class activation and eye-movement - Jia Jiayi; Zhao Tianjiao; Yang Junyu; Wang Qian (Journal of Eye Movement Research)
The evaluation of design results plays a crucial role in the development of design. This study presents a design work evaluation system for design education that assists design instructors in conducting objective evaluations.